DEVELOPMENT OF INTERACTIVE SIGN LANGUAGE LEARNING VIDEOS TO IMPROVE INITIAL READING SKILLS - Anisa Marliana; Fithri Meiliawati; Sabri Sabri (PIONIR: JURNAL PENDIDIKAN, 2025)
The purpose of national education as stated in Law Number 20 of 2003 is to develop the potential of students to become human beings who have faith, piety, and noble character, as well as capable, creative, and independent. However, in practice, students with disabilities, especially deaf people, still face obstacles in obtaining equal educational services. This research aims to develop interactive learning video media based on sign language to improve the initial reading ability of deaf students. The method used is Research and Development with the ADDIE development model consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. The product was developed in the first grade Indonesian subject with body recognition material, and tested by media experts, material experts, and through field trials. The validation results showed that the product was declared very good by material experts (97.7%) and media experts (92%), as well as good in field trials (81.29%). The t-test results showed a significant increase from the pretest score (48.33) to the posttest (90.00) with a significance of 0.001. Thus, this interactive learning video media based on sign language is effective in improving the initial reading ability of deaf students and is suitable for use in the learning process.